-2x-12=3x+3

Simple and best practice solution for -2x-12=3x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-12=3x+3 equation:


Simplifying
-2x + -12 = 3x + 3

Reorder the terms:
-12 + -2x = 3x + 3

Reorder the terms:
-12 + -2x = 3 + 3x

Solving
-12 + -2x = 3 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-12 + -2x + -3x = 3 + 3x + -3x

Combine like terms: -2x + -3x = -5x
-12 + -5x = 3 + 3x + -3x

Combine like terms: 3x + -3x = 0
-12 + -5x = 3 + 0
-12 + -5x = 3

Add '12' to each side of the equation.
-12 + 12 + -5x = 3 + 12

Combine like terms: -12 + 12 = 0
0 + -5x = 3 + 12
-5x = 3 + 12

Combine like terms: 3 + 12 = 15
-5x = 15

Divide each side by '-5'.
x = -3

Simplifying
x = -3

See similar equations:

| y^2=8y-15 | | x/x+2=4 | | 4x-9=2(2x+7) | | 11+3x=12+5x | | 0=3t-2t | | y=4tanx | | -9x-43=15-11x | | 6x-8x+2=-10 | | p-8.125=16.21 | | (-12)(-13)= | | 5r+10=3r+5-3r | | p-8.125p=16.21 | | 3x*13x+14*4=7 | | 6x-8y-9x-6y= | | x^4+18x^2+69= | | 8v-3v=25 | | -5x-7=11 | | 11x-3=10(x-5)-8 | | 4=5x-3 | | 6x^2-11x+5=3x+17 | | -x-42=4x+33 | | 126-36n=7+2n | | 6v-4=8(v-2) | | 73(3x)=10 | | -10x+2=12 | | 5x+8=4(x+6)+3 | | t^3+t^2-8m^3-4m^2=0 | | 2y-8=3y-10 | | 3(x-3)+2x-3=4x-8 | | 5x+4=8x-30 | | -2-42=4x+33 | | 15x*6=12 |

Equations solver categories